Cinema 16 - British Short Films - Percival, Brian; Scott, Ridley; Greenaway, Peter; Nolan, Christopher
A unique collection of the best short films from British filmmakers, all of which are available here to own for the first time. Includes classics from the biggest names in British film as well as award winners from new talent. Cinema16 gives short films a much needed platform and celebrates the form, but also gives filmmakers and lovers access to some great films that would otherwise be impossible to see. [www.amazon.com]
Keywords: DVD-Video